The virtual battlefield : perspectives on cyber warfare - Czosseck, Christian; Geers, Kenneth (Amsterdam ; Washington, DC : IOS Press, 2009)
"All political and military conflicts now have a cyber dimension, the size and impact of which are difficult to predict. Internet-enabled propaganda, espionage, and attacks on critical infrastructure can target decision makers, weapons systems, and citizens in general, during times of peace or war. Traditional threats to national security now have a digital delivery mechanism which would increase the speed, diffusion, and power of an attack. There have been no true cyber wars to date, but cyber battles of great consequence are easy to find. This book is divided into two sections--Strategic viewpoints and Technical challenges & solutions--and highlights the growing connection between computer security and national security"--P. 4 of cover.
pt. 2. Technical challenges and solutions. Behavioral analysis of zombie armies / Olivier Thonnard, Wim Mees, Marc Dacier -- Proactive botnet countermeasures-an offensive approach / Felix Leder, Tillmann Werner, Peter Martini -- When not to pull the plug-the need for network counter-surveillance operations / Scott Knight, Sylvain Leblanc -- Autonomic computer network defence using risk state and reinforcement learning / Luc Beaudoin, Nathalie Japkowicz, Stan Matwin -- Enhancing graph-based automated DoS attack response / Gabriel Klein ... [et al.] -- On nth order attacks / Daniel Bilar -- Business and social evaluation of denial of service attacks in view of scaling economic counter-measures / Louis-Francois Pau -- Virtual plots, real revolution / Roelof Temmingh, Kenneth Geers.
Includes indexes.
Includes bibliographical references and indexes.
Keywords: Information warfare; Cyberterrorism; Computer crimes